2021
DOI: 10.1097/iae.0000000000003215
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Three–gauge Hypersonic Vitrectomy

Abstract: Purpose: To evaluate the safety, effectiveness, and the best parameters setup of hypersonic vitrectomy.Methods: A prospective, multicentric, interventional study on 50 eyes that had undergone hypersonic vitrectomy because of various vitreoretinal diseases. We primarily assessed the effectiveness of vitreous removal, intraoperative complications, and surgical setup. Secondarily, we evaluated single-surgery anatomical success and postoperative best-corrected visual acuity.Results: Intraoperative complications oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Stanga et al reported in the first clinical cases that vitreous strands were present in the majority of cases. 19 This was better managed in Blinder’s and Romano’s study, which reported difficulties in cutting the vitreous and the presence of vitreous strands in only 13% 21 respectively in 10% 22 of cases. With ongoing further clinical studies and machine parameter adaptations, this issue may be minimized.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Stanga et al reported in the first clinical cases that vitreous strands were present in the majority of cases. 19 This was better managed in Blinder’s and Romano’s study, which reported difficulties in cutting the vitreous and the presence of vitreous strands in only 13% 21 respectively in 10% 22 of cases. With ongoing further clinical studies and machine parameter adaptations, this issue may be minimized.…”
Section: Discussionmentioning
confidence: 90%
“…Prior research on the use of hypersonic vitrectomy with Vitesse has shown similar promising results regarding the safety and efficiency of the device. 19 , 21 , 22 Stanga et al 19 published the first human study using Vitesse on 20 patient eyes in India. In this study, surgeons were able to successfully perform peripheral vitrectomy in 18 of 20 patient eyes using hypersonic vitrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These droplets, dispersed in the aqueous phase, can vary in size, penetrate into ocular tissues, and can be detected within retina, optic nerve, cornea, iris, trabecular meshwork and ciliary body [ 61 , 62 ]. Silicone oil emulsification is influenced by the properties of the SO itself (e.g., interfacial tension and viscosity) and a variety of additional factors, such as shear stresses generated at the SO–aqueous interface during saccadic eye movements [ 63 , 64 ], presence of encircling bands [ 63 ], concomitant intraoperative use of perfluorocarbon liquids [ 65 ], energy generated by intraocular instruments [ 66 , 67 ], and the presence of compounds acting as surfactant, e.g., LMWC [ 68 ] and endogenous molecules (e.g., blood components, lipids, proteins, etc.) [ 69 , 70 , 71 , 72 ].…”
Section: Silicone Oil Emulsificationmentioning
confidence: 99%